The effect of athlete branding on endorsement perceptions among Malaysian elite academy football players / Muhammad Shazril Hidayat Mohamed Rasid ... [et al.]. - Mohamed Rasid, Muhammad Shazril Hidayat; Linoby, Adam; Md Yusoff, Yusandra; Haziq, Amrun; Zulqarnain, Muhammad; Sazali, Razif (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Athlete branding plays an important role in shaping endorsement opportunities particularly among emerging talents [1]. This study explores the perceptions of Johor Darul Takzim FC (JDT FC) academy players regarding athlete branding and its influence on potential endorsements. By addressing limited research on young athletes in elite academies and integrating branding factors with endorsement success [2]. This study highlights contextual insights critical for enhancing athletes’ marketability in a competitive sports landscape. This quantitative descriptive study utilized surveys to examine athlete branding and endorsement perceptions among 80 purposively sampled JDT FC academy players. Participants were selected for their relevance to the research objectives. Data were analyzed using JAMOVI (version 2.3.7) employing descriptive statistics and Pearson Correlation to identify key factors influencing perceptions and endorsement potential. The questionnaire was adopted and adapted from Athlete Personality model in the research of (Brad and Todd, 2013; Nguyen Minh HA, Cao Nhat Tuan, 2019).